PEMERIKSAAN KESEHATAN TELINGA PADA LANSIA DI PANTI SOSIAL LANJUT USIA MANDALIKA MATARAM - Eka Arie Yuliyani; Hamsu Kadriyan; Didit Yudhanto; Gusti Ayu Trisna Aryani; Mochammad Alfian Sulaksana; Made Ratna Dewi; I Gede Wiranugraha (Universitas Mataram, 2022)
Ear health is a condition that greatly affects a person's quality of life. Hearing is very important, especially in communication, so maintaining ear health and hygiene is mandatory. In the elderly, the organ of hearing has decreased function due to degeneration of sensory cells. In addition to the accumulation of wax in the ears, this degeneration process can affect the ability to hear for the elderly so that it can interfere with communication with people around them. The purpose of this service activity is to provide ear health services to the elderly at the Mandalika Mataram Elderly Social Institution so that it can help the elderly in terms of maintaining ear cleanliness and conducting hearing tests with audiometry. This service activity was carried out one day and was attended by 30 elderly people, where the activity was carried out by cleaning the ears and then continuing with an examination of the condition of the ears and hearing tests for the elderly at the Mandalika Mataram Social Institution for the Elderly conducted by the service team. The participants were very enthusiastic about participating in this service activity. Based on the data collected, there were 3 participants who experienced moderate to severe hearing loss, 3 people with chronic suppurative otitis media, and 15 people with cerumen in one ear or both ears and the other was in good condition. These results illustrate the need for hearing screening activities, ENT health services and education to maintain ear hygiene in order to improve the quality of life of the elderly.